Methodology of imputed rent: rethinking of the own housing costs - Shcherbyna, A. (Ways to Improve Construction Efficiency, 2022)
International comparisons of household expenditures on housing and communal services, despite a significant increase in tariffs, indicate an unreasonably low absolute and relative level of these expenditures in Ukraine. Analyzing this problem, the article considers the concept of conditional (imputed) rent (rent), which in recent years has been used as macroeconomic statistics and statistics on income and living conditions. The need to reliably determine the conditional rent is due to the differences in the formation of annual expenditures and incomes of households living in their own homes and those who rent housing. The aim of the article is, however, to compare the statistical expenditures of households on housing and communal services, in particular on housing maintenance services in cases where households are homeowners or tenants and national statistical observations differ in the methods of determining conditional rent or no such definition at all. The research methodology in this article deals with the definition of conditional rent in Ukraine in scientific publications on housing economics. Such publications are intended to clarify the idea of the full cost of homeowners necessary for its normal reproduction. Therefore, it is important how perfect the methodology for determining the conditional rent abroad is and how domestic statistics determine (or do not determine at all) the conditional rent. The results of the study indicate the general problems of determining the conditional rent, related to the incompleteness of the information base required for calculations. At the same time, in domestic practice there is a methodological gap in the reflection of conditional rent in macroeconomic statistics of final consumption expenditures of households and the lack of a corresponding indicator in sample surveys of income and expenditure (living conditions). It is concluded that correct comparisons in domestic surveys, further improvement of housing statistics and adjustment of absolute and relative indicators of household expenditures using their own housing, and thus an overall increase in the share of expenditures on housing services.